1997
DOI: 10.1292/jvms.59.521
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Immunolocalization of Steroidogenic Enzymes in the Testes of the Japanese Black Bear (Ursus thibetanus japonicus).

Abstract: ABSTRACT. Seasonal changes in sites of immunostaining of steroidogenic enzymes were examined in testes of the Japanese black bear, Ursus thibetanus japonicus. In addition, serum concentrations of testosterone and estradiol-17β were investigated by radioimmunoassay, and the seasonal changes were compared with the results of immunostaining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
36
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 40 publications
14
36
1
1
Order By: Relevance
“…Immunohistochemical studies by Goyal et al [7] have detected androgen receptor in the developing testis (1-19 weeks old) and excurrent ducts of the rat. 3βHSD is the predominant regulator of testosterone production in Leydig cells [12,17]. The present findings on the expression of 3βHSD show an agerelated rise in testes, which is in accordance with these earlier reports.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Immunohistochemical studies by Goyal et al [7] have detected androgen receptor in the developing testis (1-19 weeks old) and excurrent ducts of the rat. 3βHSD is the predominant regulator of testosterone production in Leydig cells [12,17]. The present findings on the expression of 3βHSD show an agerelated rise in testes, which is in accordance with these earlier reports.…”
supporting
confidence: 93%
“…The present study showed that P450scc, 3βHSD, P450c17 and P450arom were well localized in adult Leydig cells. In some mammals, P450arom is localized in Leydig cells, Sertoli cells and germ cells [12,24,25]. However, in rams [3], stallions [1], humans [10] and boars [4], P450arom was localized only in Leydig cells.…”
mentioning
confidence: 99%
“…In accordance with the findings in other mammalian species [10,11,21,22], the present study detected the metabolic enzymes from cholesterol to androstenedione (P450scc, 3βHSD and P450c17) in interstitial tissue of the Japanese black bear testis. These results are also in agreement with the immunohistochemical localization of these three enzymes in the Japanese black bear testis [2,9]. This strongly suggests that androstenedione is synthesized in the interstitial tissue, probably in Leydig cells in the bear.…”
Section: Discussionsupporting
confidence: 89%
“…Also, there are several reports at the protein level based on the immunohistochemical method in wild animals like brown bears [8], black bears [2,9], raccoon dogs [10] and deer [11]. However, there have been few reports on the gene expression of steroidogenic enzymes in the testes of wild mammals.…”
mentioning
confidence: 99%
“…Aromatase protein expression differs seasonally in bank vole (Clethrionomys glareolus) testes (Bilinska et al, 2000), as do testicular 3β-hydroxysteroid dehydrogenase concentrations , 2001b. ) in Japanese black bears (Ursus thibetanus japonicus) (Komatsu et al, 1997). Expression of these steroidogenic enzymes and other regulatory factors may also differ in other seasonally breeding species, affecting local apoptotic activity.…”
Section: Role Of Testosteronementioning
confidence: 99%